Effectiveness of Digital Marketing Strategies and Political Brand Reinforcement - Manek, Daniel; Fadah, Isti (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2024)
This research explores the relationship between the effectiveness of digital marketing strategies and the strengthening of political brands in the context of political choices and public perceptions. Amidst the shifting political paradigm increasingly driven by digital media, a deeper understanding of how digital marketing strategies influence the image and impressions of political leaders becomes increasingly important. This study employs a descriptive qualitative approach supported by quantitative data on the level of digital media usage as a promotional tool for political party candidates. Data analysis is conducted by referring to the results of literature studies and political phenomenon studies to discover the relationships and implications between variables of digital marketing strategies and the strengthening of political brands. Findings indicate that the effectiveness of digital marketing strategies significantly contributes to the strengthening of political brands, with various elements such as content quality, social interaction, and online presence playing key roles in shaping public perceptions of a political leader.The results of this research provide valuable insights for political marketing practitioners in developing more effective strategies in optimizing the use of digital media to reinforce political identities and images. Practical implications of this research also pave the way for future researchers to further explore the dynamics of interaction between digital marketing strategies and the formation of political brands in the ever-changing context of modern politics. Keywords : Marketing Strategy, Branding, Digital, Communication.